Investigation of Technical Equipment in Computer Stereo Vision: Camera Calibration Techniques - Serafinavičius, P. (Elektronika ir Elektrotechnika, 2005)
This paper describes one of the most important steps in computer stereo vision – camera calibration. Techniques developed by various researchers have been investigated. Analysis of internal and external calibration parameters, classification of the calibration techniques by the mathematical apparatus (closed-form solution, nonlinear optimization, two steps methods), calibration processes (photogrammetric, auto-calibration), advantages and disadvantages of them are provided here. Ill. 2, bibl. 7 (in English; summaries in Lithuanian, English and Russian).